Memory as a mediator between depression and academic achievement among Iranian adolescents. - Fayegh, Yousefi; Redzuan, Ma’rof; Mansor, Mariani; Abu Talib, Mansor; Juhari, Rumaya (2009)

(untitled)
The purpose of this paper is to determine the mediation effect of memory on the relationship between depression and academic achievement. The paper is based on a study, which was carried out among adolescents in Iran. The respondents of the study were 400 adolescents (200 males and 200 females) in the age range of 15-19 years old. Instruments used for data collection were the Beck Depression Inventory (21 items) and the Wechsler Memory Scale – 3rd Edition (WMS-III). The finding shows that depression significantly affected academic achievement and this relationships is mediated by memory (Z=1.65, p≤ 0.). Thus, it is recommended to enhance academic achievement and mental health in school settings, support strategies such as educational guidance and counseling. Teaching life skill programs and psychotherapy should be promoted.